2009
DOI: 10.1177/1359105309340977
|View full text |Cite
|
Sign up to set email alerts
|

Comparing views of patients, parents, and clinicians on emotions in anorexia

Abstract: Patients with anorexia nervosa (AN) may experience difficulties in emotional processing that can adversely affect treatment and maintenance of the illness. Focus groups or questionnaires were undertaken with patients with AN, parents and clinicians, with the aim to explore the most salient issues pertaining to emotions and social cognition in AN. Qualitative thematic analysis was used to analyse the data. Seven primary themes were identified showing congruence across groups: 'emotional awareness and understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 19 publications
5
90
0
1
Order By: Relevance
“…In addition, this study supports Waller et al (2003) and Fox and Harrison (2008) who have noted the prominence of dysregulated angry emotions in individuals with EDs. Diffi culties in managing and coping with social situations were also noted in a qualitative study (Kyriacou, Easter, & Tchanturia, 2009).…”
Section: Comparisons With Findings In the Eating Disorder Literaturementioning
confidence: 81%
“…In addition, this study supports Waller et al (2003) and Fox and Harrison (2008) who have noted the prominence of dysregulated angry emotions in individuals with EDs. Diffi culties in managing and coping with social situations were also noted in a qualitative study (Kyriacou, Easter, & Tchanturia, 2009).…”
Section: Comparisons With Findings In the Eating Disorder Literaturementioning
confidence: 81%
“…Moreover, qualitative studies have reported that participants who have experienced AN think that being able to communicate their emotions and to develop supportive relationships are key aspects of recovery (Rance et al, 2015;Federici and Kaplan, 2008;Jenkins and Ogden, 2012;Kyriacou et al, 2009). Facial expressions of positive emotions, such as the smile, are essential for establishing rapport (TickleDegnen, 2006) and are related to cooperative intentions (Schmidt and Cohn, 2001), as well as social rewards (Shore and Heerey, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach in designing this clinical intervention was based on both extensive input from stakeholders, patients, clinicians and carers, 183 and recent findings from experimental studies. 16,184,185 The three studies reported here used mixed methods to provide an initial evaluation of CREST in individual format.…”
Section: Discussionmentioning
confidence: 99%